The effect of accommodation on peripheral refraction under two illumination conditions - van Ginkel, Raquel (2022)
The clinical importance of peripheral refraction as a function of accommodation has become increasingly evident in the last years with special attention given to myopia control. Low order ocular aberrations were measured with a Hartmann–Shack aberrometer in a sample of 28 young emmetropic subjects. A stationary Maltese cross was presented at 2.5 D and 5.0 D of accommodative demand and at 0°, 10° and 20° of eccentricity in the horizontal visual field under two different illumination conditions (white and red light). Wavefront data for a 3 mm pupil diameter were analyzed in terms of the vector components of refraction (M, J0 and J45) and the relative peripheral refractive error (RPRE) was calculated. M was myopic at both accommodative demands and showed a statistically significant myopic increase with red illumination. No significant change in J0 and J45 was found with accommodation nor between illumination conditions. However, J0 increased significantly with eccentricity, exhibiting a nasal-temporal asymmetry. The RPRE was myopic at both accommodation demands and showed a statistically significant hyperopic shift at 20° in the nasal retina. The use of red light introduced statistically and clinically significant changes in M, explained by the variation of the ocular focal length under a higher wavelength illumination, increasing the experimental accommodative demand. These findings may be of relevance for research exploring peripheral refraction under accommodation, as the choice of target illumination is not trivial.